Study of Formulation, Characteristics, and Evaluation of Self Nanoemulsifying Drug Delivery System (SNEDDS) for Atorvastatin Calcium - Silvia, Nurfianti; Rusdiana, Taofik; Gozali, Dolih; Husni, Patihul (Indonesian Journal of Pharmaceutics, 2023)
A Self-Nanoemulsifying Drug Delivery System (SNEDDS) is a formulation approach used in the pharmaceutical and biotechnology industries to improve the solubility and bioavailability of poorly water-soluble drugs. Atorvastatin calcium has limited water solubility, which can affect its bioavailability when administered orally. Its solubility can be enhanced by various formulation techniques, such as the use of self-nanoemulsifying drug delivery systems (SNEDDS). The purpose of this study is to determine the formulation and characterization of SNEDDS and determine how it affects the bioavailability of atorvastatin calcium. The data were collected from published journals. The carrier components required in the formulation of atorvastatin calcium with SNEDDS formulation include oils (oleic acid, peceol, capyrol 90, and capmul CMC), surfactants (tween 80, tween 20, labrasol, cremophor RH 40) and co-surfactants (brij 30, propylene glycol, transcutol-P, PEG 400, transcutol HP). Characterization of atorvastatin calcium with SNEDDS formulation showed droplet size 21.6-162.2 nm; zeta potential -1.32 - 24.6±6.47 mV; and polydensity index 0.164 - 0.297. SNEDDS formulation increased the percentage of drug release and increased the bioavailability of atorvastatin calcium. Keywords: self-nanoemulsifying drug delivery system, SNEDDS, atorvastatin                      calcium, formulation, characteristics, dissolution, bioavailability